1970
DOI: 10.1111/j.1365-3180.1970.tb00921.x
|View full text |Cite
|
Sign up to set email alerts
|

The Interaction of Paraquat With Soil: Adsorption by an Expanding Lattice Clay Mineral

Abstract: Summary. Some characteristics of the interaction of paraquat with a dioctahedral montmorillonite have been studied by a combination of adsorption, radioisotope exchange, and X‐ray diffraction techniques. The clay exhibited a high affinity for paraquat, since when less than 50 me/100 g were absorbed no paraquat was detected in the solution (<0·07 ppm), irrespective of the saturating cation, and in the presence or absence of 3·5 M ammonium nitrate solution. Interlamellar adsorption of paraquat was detected by t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
9
0

Year Published

1973
1973
2003
2003

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(11 citation statements)
references
References 11 publications
2
9
0
Order By: Relevance
“…While paraquat was adsorbed by montmorillonite in amounts approximately equal to the CEC of the clay, the amounts of diquat adsorbed were slightly less than the CEC. In general, the data are in accordance with those reported by other workers on the adsorption of diquat and paraquat by montmorillonite (Weber and Weed, 1968;Weed and Weber, 1969;Knight and Denny, 1970;Damanakis et al, 1970). The adsorption of the two herbicides by the organo-clay complex followed nearly the same pattern as was observed for the pure clay, but the amounts adsorbed by the former on 'per unit weight basis' were considerably lower than the latter.…”
Section: Resultssupporting
confidence: 92%
“…While paraquat was adsorbed by montmorillonite in amounts approximately equal to the CEC of the clay, the amounts of diquat adsorbed were slightly less than the CEC. In general, the data are in accordance with those reported by other workers on the adsorption of diquat and paraquat by montmorillonite (Weber and Weed, 1968;Weed and Weber, 1969;Knight and Denny, 1970;Damanakis et al, 1970). The adsorption of the two herbicides by the organo-clay complex followed nearly the same pattern as was observed for the pure clay, but the amounts adsorbed by the former on 'per unit weight basis' were considerably lower than the latter.…”
Section: Resultssupporting
confidence: 92%
“…During the past few years much work has been published on the adsorption of diquat and paraquat by mineral soils, clays, and charcoal (Calderbank 1968;Damanakis et al 1970;Faust and Zarins 1969; Knight and Denny 1970;Weber et al 1965;. However, little is known about the interaction of bipyridylium herbicides with humic substances, the principal organic components of soils and waters.…”
Section: Introductionmentioning
confidence: 99%
“…Thus it is concluded that guazatine was preferentially adsorbed by soil inorganic fraction, and this is quite similar to bipyridinium herbicides. 6,11,[14][15][16] Predominant mechanism for the adsorption of guazatine to soil is considered to be an ion exchange, since the pKa values of guanidine and imino groups of the fungicide are greater than 13 and 9, respectively; consequently the fungicide is regarded as existing predominantly as a trivalent cation in neutral environment. It can be satisfactorily explained by this mechanism that guazatine was adsorbed to Chiba soil to the extent of normal CEC.…”
Section: Discussionmentioning
confidence: 99%